THE MUCUS OF Helix aspersa AS AN ANTI-INFLAMMATORY AND ANTIBACTERIAL TREATMENT TOWARDS MULTIDRUG-RESISTANT BACTERIA FROM INFECTED WOUNDS - MERAH, NESMA; BOUACHA, MABROUKA; BESNACI, SANA; KOUCH, MINA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
The mucus of snails is known for its high content of bioactive substances, which can be effective in the treatment of infected wounds. The objective of this study is to evaluate the antibacterial and anti-inflammatory activity of three extracts of Helix aspersa mucus. The evaluation of the antibacterial activity of mucus extracts was carried out against three Gram-negative bacteria isolated from infected wounds using the well diffusion method, the microdilution for the minimum inhibitory concentrations (MIC) determination, and minimum bactericidal concentrations (MBC) determination. The anti-inflammatory activity was carried out using albumin denaturation inhibition and the human red blood cell membrane stabilization methods. The results obtained showed that snail mucus extracts possess an inhibitory effect on the growth and viability of Gram-negative bacteria. The inhibitory diameters ranged between 09.33±1.11 and 12.00±0.77 mm, the MIC was 25 % (v/v), and the MBC ranged between 25 and 50 % (v/v). The minimum bactericidal concentrations/minimum inhibitory concentrations (MBC/MIC) ratios indicate that snail mucus possesses a bacterial effect on Gram-negative bacteria. Furthermore, snail mucus possesses an anti-inflammatory effect through the inhibition of protein denaturation and membrane stabilization. The results obtained from this study encourage the use of Helix aspersa mucus in clinical practice as an antibacterial and anti-inflammatory agent in the treatment of infected wounds.